University of Wisconsin-River Falls instructional staff views and attitudes towards student athletes on campus - Novacheck, Bradley (My University, 2012)
In the growing world of college athletics we are beginning to see some issues with student-athletes. Many are believed to be considered the dumb jock, the party animal, or worse. Many also believe student athletes are considered hard workers and put efforts into academics and the respective athletic activity. The purpose of this study is to determine whether there are different perceptions of student-athletes from University of Wisconsin-River Falls Instructional staff members in classes and with class work at UWRF. There have been possibilities of both positive and negative views with student-athletes and this issue needs to be seen on a higher level. Previous research relates into the ideas, attitudes and judgments shared by faculty as well as other students on other campuses. Using a mixed methods approach of using both quantitative and qualitative research, the researcher will determine a possible relationship. This study was not meant to attack but identify the possibility of mistreatment if any at the college level. A survey was conducted by gaining a random sample of the UWRF student population and all 392 members of the UWRF Instructional staff. The survey included questions on the perceptions of student athletes from the instructional staff points of view. Both students and instructional staff were asked to participate because of insight the two sides can provide on interactions between instructional staff and student athletes. The research indicated that UWRF instructional staff members do not have any preconceived notions or attitudes towards student athletes at UWRF. There was insight brought in by open ended questions provided by both the students and the UWRF instructional staff. It did bring a negative connotation to the main idea presented, but only in a few cases. It has become evident that there was a possibility of mistreatment because of stereotypes and one student athlete at UWRF causing possible problems creating tension between select UWRF Instructional staff members.
Thesis (M.S.)--University of Wisconsin-River Falls, 2012. 54 leaves. Includes bibliographical references (leaf 40).
Keywords: Student athletes; College sports; College athletes; College athletes--Wisconsin--River Falls; University of Wisconsin-River Falls--Faculty--Attitudes